The effect of overcrowding in the US school System, A simulation approach - Mubarak Banisakher; Pamela McCauley (Journal of Education and Learning (EduLearn), 2017)
This study applies a simulation to analyze overcrowding (congestion) in a school system. This work aims to analyze the overcrowding and to describe a decision support system that needs to be developed to help in assessing the need for classrooms in different schools and to develop a systematic approach to improve such overcrowding. Education leaders face extraordinary challenges as the nation’s schools struggle to rise to the challenge of the No Child Left Behind Act of 2001. Education leaders are now expected to be instructional leaders, show a strong commitment to closing the achievement gap between majority and minority students, and use data to improve teaching and learning. All of this is in addition to the logistics of running a school system such as making sure that busing and meal services operate smoothly. Some researchers stated that education leadership must do much more than it has in the past (Davis, S.; Darling-Hammond, L.; LaPointe, M.; and Meyerson, D. (2005)..